3D interconnected hierarchically macro-mesoporous TiO2 networks optimized by biomolecular self-assembly for high performance lithium ion batteries. Issue 32 (14th March 2016) - Ren, Xiao-Ning; Wu, Liang; Jin, Jun; Liu, Jing; Hu, Zhi-Yi; Li, Yu; Hasan, Tawfique; Yang, Xiao-Yu; Van Tendeloo, Gustaaf; Su, Bao-Lian
Abstract : A 3D interconnected hierarchically macro-mesoporous TiO2 network optimized by the mediation of biomolecular self-assembly has been used for high performance lithium storage. Abstract : Biomolecular self-assembly is an effective synthesis strategy for material fabrication with unique structural complexity and properties. For the first time, we integrate inner-particle mesoporosity in a three-dimensional (3D) interconnected macroporous TiO2 structure via the mediation of biomolecular self-assembly of the lipids and proteins from rape pollen coats and Pluronic P123 to optimize the structure for high performance lithium storage. Benefitting from the hierarchically 3D interconnected macro-mesoporous structure with high surface area, small nanocrystallites and good electrolyte permeation, such a unique porous structure demonstrates superior electrochemical performance, with high initial coulombic efficiency (94.4% at 1C) and a reversible discharge capacity of 161, 145, 127 and 97 mA h g −1 at 2, 5, 10 and 20C for 1000 cycles, with 79.3%, 89.9%, 90.1% and 87.4% capacity retention, respectively. Using SEM, TEM and HRTEM observations on the TiO2 materials before and after cycling, we verify that the inner-particle mesoporosity and the Li2 Ti2 O4 nanocrystallites formed during the cycling process in interconnected macroporous structure greatly enhance the cycle life and rate performance. Our demonstration here offers opportunities towards developing and optimizing hierarchically porous structures for energy storage applications via biomolecular self-assembly.